Prioritizing development policy research in Sudan: An innovative approach to guide IFPRI’s Sudan Strategy Support Program - Kirui, Oliver K.; Siddig, Khalid; Breisinger, Clemens; Dorosh, Paul A.; Kassim, Yumna (International Food Policy Research Institute, 2022)
This paper presents an innovative approach to prioritizing development policy research in Sudan with the specific objective of informing the research agenda of the Sudan Strategy Support Program (Sudan SSP) of the International Food Policy Research Institute (IFPRI). The key steps in this process were: A review of relevant priority setting methods and existing government strategies, Pre-selection of research themes, Selection of national and international experts, Design and conduct priority setting workshop; and Priority matrix construction and paper writing. The paper suggests key research priorities for Sudan, which are both highly relevant to Sudan’s current and future development policy agenda and consistent with IFPRI’s own comparative advantage and strategy. It identifies research areas and topics under five main themes, namely: 1. Agricultural production, 2. Markets and trade, 3. Livelihoods and nutrition, 4. Development strategy and investment planning, and 5. Increasing resilience of farming under growing climate challenges. Tackling the priority research tasks identified in this paper, for these five themes, is expected to help reduce poverty and improve food and nutrition security in Sudan. However, strengthening the links between policy research and decision-making will be crucial to ensure that evidence-based solutions are relevant and have a positive impact on people’s lives.